2019
DOI: 10.1038/s41467-019-13048-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong UV/mechano-excited room temperature phosphorescence from purely organic cluster excitons

Abstract: Purely organic room temperature phosphorescence (RTP) has attracted wide attention recently due to its various application potentials. However, ultralong RTP (URTP) with high efficiency is still rarely achieved. Herein, by dissolving 1,8-naphthalic anhydride in certain organic solid hosts, URTP with a lifetime of over 600 ms and overall quantum yield of over 20% is realized. Meanwhile, the URTP can also be achieved by mechanical excitation when the host is mechanoluminescent. Femtosecond transient absorption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
198
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 275 publications
(204 citation statements)
references
References 50 publications
3
198
0
3
Order By: Relevance
“…Cluster excitons, proposed recently by Tang et al, are another archetypical property of two-component aggregates with strong intermolecular interaction. [250] As shown in Figure 17A, a group of electron-deficient compounds was chosen for the host-guest combination and, from them, the more conjugated 1,8-naphthalic anhydride (NA) was selected as guest and the other three compounds, pentachloropyridine (PCP), phthalic anhydride (PA), and 1,2-dicyanobenzene (DCB) were set as hosts. Photophysical characterization showed that NA and PA only showed phosphorescence at 77K without showing any RTP.…”
Section: Two-component Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster excitons, proposed recently by Tang et al, are another archetypical property of two-component aggregates with strong intermolecular interaction. [250] As shown in Figure 17A, a group of electron-deficient compounds was chosen for the host-guest combination and, from them, the more conjugated 1,8-naphthalic anhydride (NA) was selected as guest and the other three compounds, pentachloropyridine (PCP), phthalic anhydride (PA), and 1,2-dicyanobenzene (DCB) were set as hosts. Photophysical characterization showed that NA and PA only showed phosphorescence at 77K without showing any RTP.…”
Section: Two-component Aggregatesmentioning
confidence: 99%
“…However, in NA/PCP aggregates, the NA/PCP cluster is excited as a whole to form transient states of S 1(Cluster) and T 1(Cluster) with efficient ISC. After that, the lowest triplet state of guest (T 1(NA) ) serves as the energy "trap" to "attract" energy transfer from [250] Copyright 2019, The Authors, published by Springer Nature.…”
Section: Two-component Aggregatesmentioning
confidence: 99%
“…More recently, host–guest chemistry has witnessed its tremendous preponderance in pursuit of efficient RTP with long lifetime, which relies on the host–guest interactions for unique aptitude in stabilizing triplet energy and promoting ISC, such as doping organic phosphors into a suitable matrix, [ 7 ] co‐crystallization of two components, [ 8 ] melt‐casting blend, [ 9 ] and construction of coordination polymers (CPs). [ 10 ] However, the two‐way selection of the host and the guest ineluctably empowers these strategies with lack of universality.…”
Section: Introductionmentioning
confidence: 99%
“…rganic afterglow materials, which typically show a luminescent lifetime over 0.1 s according to the resolving limit of the naked eyes, have attracted tremendous attention recently [1][2][3] . By the significant breakthrough of the excited state lifetime tuning of the highly active organic excitons, innovational applications of organic afterglow molecules in various fields such as biological imaging, information storage, sensing, and security protection have been witnessed [4][5][6][7] . However, owing to the organic ultralong room temperature phosphorescence (OURTP) nature of organic afterglow through the spin-forbidden radiative decay of the triplet excited states (T 1 ), it is a crucial challenge to achieve high afterglow efficiency 8,9 .…”
mentioning
confidence: 99%